Wiley Blackwell Companion to Karl Barth - Hunsinger, George; Johnson, Keith L. (Wiley Blackwell, 2020)
The most comprehensive scholarly survey of Karl Barth's theology ever published Karl Barth, arguably the most influential theologian of the 20th century, is widely considered one of the greatest thinkers within the history of the Christian tradition. Readers of Karl Barth often find his work both familiar and strange: the questions he considers are the same as those Christian theologians have debated for centuries, but he often addresses these questions in new and surprising ways. The Wiley Blackwell Companion to Karl Barth helps readers understand Barth's theology and his place in the Christian tradition through a new lens. Covering nearly every topic related to Barth's life and thought, this work spans two volumes, comprising 66 in-depth chapters written by leading experts in the field. Volume One explores Barth's dogmatic theology in relation to traditional Christian theology, provides historical timelines of Barth's life and works, and discusses his significance and influence. Volume Two examines Barth's relationship to various figures, movements, traditions, religions, and events, while placing his thought in its theological, ecumenical, and historical context. This groundbreaking work: Places Barth into context with major figures in the history of Christian thought, presenting a critical dialogue between them Features contributions from a diverse team of scholars, each of whom are experts in the subject Provides new readers of Barth with an introduction to the most important questions, themes, and ideas in Barth's work Offers experienced readers fresh insights and interpretations that enrich their scholarship Edited by established scholars with expertise on Barth's life, his theology, and his significance in Christian tradition An important contribution to the field of Barth scholarship, the Wiley Blackwell Companion to Karl Barth is an indispensable resource for scholars and students interested in the work of Karl Barth, modern theology, or systematic theology.